First Impressions: A Review of Diversity-related Content on North American LIS Program Websites - Ana Ndumu; Crystal Betts-Green (The International Journal of Information, Diversity, & Inclusion, 2018)
This study explores library and information science (LIS) program websites from a recruitment and marketing standpoint and sheds light on the availability of diversity - related content. LIS and higher education literature suggests that the Internet and program websites are crucial when it comes to prospective students’ graduate school selection. Using Berelson’s (1952) quantitative content analysis technique, the researchers examined faculty profiles, diversity statements, diversity-related courses, funding opportunities, achievements, and student organizations on program websites. The data indicates that, collectively, LIS programs are successful in sharing information on funding as well as highlighting faculty scholarship related to diversity. Greater emphasis could be placed on crafting and displaying diversity statements; designing, offering, and listing diversity - related courses beyond survey courses; consistently showcasing diversity-related achievements and events; and encouraging and supporting diversity-related student groups. This research has implications for fostering more strategic diversity-related initiatives.